A CRITICAL STUDY ON THE SOCIO-TECHNOLOGICAL FACTORS INFLUENCING GREEN SUPPLY CHAIN MANAGEMENT IN THE HEALTHCARE INDUSTRY; MUMBAI REGION - Paharia, Apurve; Khatri, Akshay; Jain, Prasham; (Dr), Jinu Kurian (IJRDO - Journal of Business Management, 2017)
In this ever evolving world of automation, industrial marvels and increasing ease of usage, it is extremely important to give due diligence to environment and eradicate or optimize processes that degrade sustainability at any cost. We have taken Healthcare sector into consideration because this is the only sector where products are used to deliver service which forms the basis of supply chain system. The study projected here consists of effect of contemporary independent variables on GSCM. To further carry forward our analysis, we created a theoretical framework consisting of all the factors depicting relationship between them. In order to gather data, we prepared a questionnaire to know the responses of how GSCM is currently been practiced in healthcare sector and after a successful survey we got certain datasets for analysis. Finally, a series of correlation analysis between different parameters was performed and the results were cross referenced with the objectives carving a direction for future research and deducing that this research was successful in order to plot impactful factors to implement GSCM.